Analisis Pengaruh Konsumsi, Investasi, dan Ekspor Terhadap Pertumbuhan Ekonomi Indonesia Masa Pandemi Tahun 2020-2021 - Aqilla Fadia Haya; Sri Indah Nikensari; Siti Nurjanah (Yayasan Education and Social Center, 2022)
The impact of the pandemic is also caused not only in the health sector but also in the economic and social fields. At the beginning of the pandemic, the Indonesian economy was surprised by the growth that fell sharply, which was -5.32% in the second quarter of 2020. The negative economic growth was caused by a decline in economic growth factors, one of which can be seen through the expenditure approach. This study aims to analyze the effects of consumption, investment, and exports on Indonesia's economic growth during the pandemic. The method used is quantitative, with the help of statistical applications, E-Views 9, with panel data regression techniques in 34 provinces in Indonesia. The results of this study show that household consumption, Foreign Direct Investment, and exports have a positive and significant impact on economic growth. On the other hand, domestic investment has a negative and significant impact on economic growth in Indonesia. Simultaneously, the relationship between household consumption, FDI, DI, and exports can explain economic growth through an expenditure approach without including government spending and imports. The results of the Random Effect Model found that the greatest influence obtains from FDI, exports, household consumption, and DI, respectively. It is due to the pandemic, which has caused economic activity in the most likely expenditure to encourage production activities, which is foreign investment. Furthermore, exports have the second largest impact on economic growth during the pandemic. On the other hand, domestic investment has a negative effect due to an increase in the number of realized investments during a decline in economic growth during the pandemic, in addition to a decrease in production and distribution activities, causing investors and investors to reduce investment in several areas in inequality during the pandemic